Evaluation of the QuantiFERON SARS-CoV-2 assay to assess cellular immunogenicity of the BNT162b2 mRNA COVID-19 vaccine in individuals with low and high humoral response. Issue 12 (2nd December 2021) - Tychala, Areti; Meletis, Georgios; Katsimpourlia, Eugenia; Gkeka, Ioanna; Dimitriadou, Rodoula; Sidiropoulou, Eleni; Skoura, Lemonia
ABSTRACT: Vaccines against SARS-CoV-2 are known to be less immunogenic for some individuals, whereas others present notably high levels of antibody production. We assessed the cellular response to BNT162b2 among individuals with low post-vaccination antibody levels as well as in a small group of individuals with high titers. Antibody levels were assessed by the Abbott SARS-CoV-2 IgG II Quant assay. The interferon-γ production of T-cells in response to SARS-CoV-2 antigens was determined using Qiagen's QuantiFERON SARS-CoV-2 ELISA test. Our results showed that participants with high antibody levels presented adequate cellular response in all studied cases, whereas those with low antibody levels generally showed limited to almost absent cellular response five months post vaccination.